2019
DOI: 10.1177/1687814019828585
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–structure interaction analysis of fluid pressure pulsation and structural vibration features in a vertical axial pump

Abstract: Current studies on the operation of the axial pump mainly focus on hydraulic performances, while the coupled interaction between the fluid and structure attracts little attention. This study aims to provide numerical investigation into the vibration features in a vertical axial pump based on two-way iterative fluid–structure interaction method. Three-dimensional coupling model was established with high-quality structured grids of ADINA software. Turbulent flow features were studied under design condition, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Tan et al [9] performed a numerical analysis to investigate the influence of blade rotational angle on pressure pulsation and proved that the main frequency of pressure pulsation in impeller was dominated by shaft frequency or blade frequency. Furthermore, Zhang et al [10] explored the relationship between fluid pressure pulsation and structural vibration characteristics of a vertical axial pump. It was confirmed that the rotating blades had similar frequency characteristics in both the fluid domain and the solid domain.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [9] performed a numerical analysis to investigate the influence of blade rotational angle on pressure pulsation and proved that the main frequency of pressure pulsation in impeller was dominated by shaft frequency or blade frequency. Furthermore, Zhang et al [10] explored the relationship between fluid pressure pulsation and structural vibration characteristics of a vertical axial pump. It was confirmed that the rotating blades had similar frequency characteristics in both the fluid domain and the solid domain.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [16] quantitatively analyzed the blade deformation and stress distribution of the bidirectional axial-flow pump device under different flow conditions, and found that the maximum deformation and stress existed at the blade edge and the hub respectively. Zhang et al [17] discovered that the stress concentration on the blade hub was caused by the cantilever structure of the rotating blade. Li et al [18,19] conducted bidirectional FSI and modal analyses on the mixed-flow pump, and the results shown that fatigue failure was more likely to occur at the hub and the natural frequency of vibration was not affected by the flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Figure17. Vibration mode shape in each order modal of the full tubular pump: (a) First-order mode, (b) Second-order mode, (c) Third-order mode, (d) Fourth-order mode, (e) Fifth-order mode, (f) Sixth-order mode.…”
mentioning
confidence: 99%
“…Pei J et al [12] quantitatively analyzed the blade deformation and stress distribution of the bidirectional axial-flow pump device under different flow conditions, and found that the maximum deformation and stress exist at the blade edge and the hub respectively. Zhang LJ et al [13] discovered that the stress concentration at the blade hub is caused by the cantilever structure of the rotating blade. Li W et al [14][15] conducted bidirectional FSI and modal analysis on the mixed-flow pump, and the results showed that fatigue failure was more likely to occur at the hub.…”
Section: Introductionmentioning
confidence: 99%